Electrochemical hydrogen pump for recirculation of hydrogen in a fuel cell stack - Barbir, Frano; Gorgun, Haluk (SPRINGER, 2007)
The objective of this work is to evaluate the use of an electrochemical hydrogen pump for recirculation of hydrogen in a fuel cell stack. The hydrogen pump needed about 130 mV at 0.5 A cm(-2), primarily because of the cell resistance (0.18 Omega cm(2)). This voltage loss was higher than a fuel cell voltage gain resulting from hydrogen recirculation. However, if one pumping cell is used for 10 active cells this means 13 mV loss per cell (or about 2%) which may be an acceptable voltage penalty. A stack with hydrogen recirculation should operate with less voltage fluctuation and should need purging less often than a stack operating with a dead-end mode of hydrogen supply. An additional benefit of hydrogen purification may be achieved in the systems with a fuel processor where operation in a dead-end mode is not possible. Attention must be paid to water management when designing and operating a hydrogen pump within a fuel cell stack.
Keywords: electrochemical compressor; electrochemical pump; hydrogen recirculation; Electrochemistry